2017
DOI: 10.3390/f8100355
|View full text |Cite
|
Sign up to set email alerts
|

Does the Slope of the Self-thinning Line Remain a Constant Value across Different Site Qualities?—An Implication for Plantation Density Management

Abstract: Abstract:The self-thinning rule is regarded as one of the most important principles in plantation management. This rule, involving the assumption of a constant slope coefficient, has been universally applied when regulating stand density. In this study, we hypothesized that the slope coefficient can change significantly with changes in site quality. To test this hypothesis, we first grouped forest plots into 5 categories based on site index. Second, we produced the self-thinning line represented by the Reineke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 77 publications
0
10
0
1
Order By: Relevance
“…Live tree density is expected to decline as trees grow in size, owing to increased individual demand for resources and growing space (i.e., competition) 16 , 23 . The expected magnitude of change in tree density, given some change in average tree size, varies considerably across forest communities 63 , site conditions 64 , and stand age classes 23 . Thus, we posit it is useful to contextualize observed changes in live tree density relative to those expected given shifts in average tree size within a stand.…”
Section: Methodsmentioning
confidence: 99%
“…Live tree density is expected to decline as trees grow in size, owing to increased individual demand for resources and growing space (i.e., competition) 16 , 23 . The expected magnitude of change in tree density, given some change in average tree size, varies considerably across forest communities 63 , site conditions 64 , and stand age classes 23 . Thus, we posit it is useful to contextualize observed changes in live tree density relative to those expected given shifts in average tree size within a stand.…”
Section: Methodsmentioning
confidence: 99%
“…This rule was supported by Yoda et al (1963) but researchers in Europe have often questioned it (Pretzsch and Biber 2005;Vacchiano 2005;Castagneri et al 2008). Recent studies demonstrated the need to evaluate the slope of plotted curves according to site quality (Ge et al 2017), and biases could result from the log-transformation of the data (Smith 1993), and questions have been raised on its biological validity (Packard 2014). Despite this, the use of logtransformed data versus nonlinear regression for analysing biological power laws remains a common approach.…”
Section: Introductionmentioning
confidence: 91%
“…?, respectively. The use of PWL is generally dropped in favour of logarithmic transformation of the data fitted using an ordinary least squares (OLS) function (Reineke 1933;Pretzsch and Biber 2005;Shaw 2006;Ge et al 2017). In this case, Eq.…”
Section: Introductionmentioning
confidence: 99%
“…Self-thinning is presumed to be a process intrinsic to many managed and unmanaged terrestrial plant communities, whose composition and structure are influenced by competition for resources available proportionally to space-whether aboveground (e.g., photosynthetically active radiation) or belowground (e.g., water and nutrients) (Zhang et al, 2011;Hecht et al, 2016). Therefore, w-p temporal trajectories of self-thinning have considerable implications for forest management practices (Ge et al, 2017;Zhang et al, 2019). It is to be noted, however, that p(t) reductions due to ice storms, hurricanes, fires, diseases, or other disturbances are not considered in the w − p relations described by self-thinning.…”
Section: The Self-thinning Rulementioning
confidence: 99%